1993
DOI: 10.1093/infdis/167.3.735
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus-6 (HHV-6) Infection in Allogeneic Bone Marrow Transplant Recipients: Evidence of a Marrow-Suppressive Role for HHV-6 In Vivo

Abstract: Sixteen adults were studied for the first 100 days after allogeneic bone marrow transplant to assess the pathogenic role of human herpesvirus-6 (HHV-6) infection in patients with unexplained febrile illnesses. HHV-6 was directly isolated from the blood of 6 patients. Analysis of the clinical courses of these 16 patients revealed otherwise unexplained posttransplant marrow suppression in 5 patients. Idiopathic marrow suppression occurred more frequently in patients with concurrent HHV-6 viremia (4/6) than in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
130
0
1

Year Published

1996
1996
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(133 citation statements)
references
References 0 publications
2
130
0
1
Order By: Relevance
“…HHV-6 has recently been recognized as an opportunistic pathogen in transplant recipients. It has been demonstrated that HHV-6 is associated with fever and skin rash resembling acute graft-versus-host disease (GVHD), [4][5][6][7][8][9][10] interstitial pneumonitis, 11,12 encephalitis, 13 and bone marrow suppression 14 after bone marrow transplantation (BMT).…”
mentioning
confidence: 99%
“…HHV-6 has recently been recognized as an opportunistic pathogen in transplant recipients. It has been demonstrated that HHV-6 is associated with fever and skin rash resembling acute graft-versus-host disease (GVHD), [4][5][6][7][8][9][10] interstitial pneumonitis, 11,12 encephalitis, 13 and bone marrow suppression 14 after bone marrow transplantation (BMT).…”
mentioning
confidence: 99%
“…5,6 HHV-6 infection has some association with chronic fatigue syndrome, 7 multiple sclerosis, 8,9 hepatitis, 10 meningoencephalitis, [11][12][13][14][15] thrombocytopenia, [15][16][17] and hemophagocytic syndrome. 5,7 HHV-7 also infects in infancy or early childhood and infects persistently throughout life.…”
mentioning
confidence: 99%
“…[8][9]11,12,18 However, it has been documented that benign periodic HHV-6 reactivation occurs throughout the post-transplant period. In a study by Cone et al, 12 HHV-6 DNA was detected in PBMC by PCR in all 20 transplant patients and nine of 19 healthy control studies.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] In this population, HHV-6 has reportedly been associated with skin rashes, graft-versus-host disease, pneumonitis, sinusitis, febrile episodes, graft failure, encephalitis and in some cases with a fatal outcome. 4 While serological methods are available for determining the presence of HHV-6 infection in healthy individuals, 14 such methods have limited utility in immunocompromised patients.…”
mentioning
confidence: 99%